Kontestasi Tasawuf SunnÃ® dan Tasawuf FalsafÃ® di Nusantara - Afif Anshori, Muhammad (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2014)
This article scrutinizes the history of Islamic development in Nusantara between 15th to 18th centuries, which has been colored from theological mysticism thought. Uniquely, the discussion about the Islamic thought had influenced political perspective and led to the tragedy of mihnah (inquisition). As a result, some figures were killed and a number of treasured books were burned and destroyed. In Java, such controversy involved Shaykh Siti Jenar versus Walisongo. In Sumatera, the dispute occurred between Shaykh Hamzah Fansuri and Nurudin al-Raniri. Instead of emphasizing on substantial matters, the disagreement among these figures was, in fact, caused by the political situation at that time. The writer finds that there are, at least, three main triggering factors which lead to ideological dispute and contestation between Hamzah versus al-Raniri and Siti Jenar versus Walisongo. Theological aspect is the first causing factor. The second factor is political interest, while the third factor is genealogical similarity. Keywords: sunnî sufism, philosophy sufism, wah}dat al-wujûd. KONTESTASI TASAWUF SUNNÎ DAN TASAWUF FALSAFÎ DI NUSANTARA